Plasma proteomic profiling of young and old mice reveals cadherin-13 prevents age-related bone loss - Yang, Yong Ryoul; Kabir, Mohammad Humayun; Park, Jin Hee; Park, Jae-Il; Kang, Jae Sook; Ju, Shinyeong; Shin, Yeo Jin; Lee, Seung Min; Lee, Jaemin; Kim, Seokho; Lee, Kwang-Pyo; Lee, Soo Young; et al. (IMPACT JOURNALS LLC, 2020)
The blood exhibits a dynamic flux of proteins that are secreted by the tissues and cells of the body. To identify novel aging-related circulating proteins, we compared the plasma proteomic profiles of young and old mice using tandem mass spectrometry. The expression of 134 proteins differed between young and old mice. We selected seven proteins that were expressed at higher levels in young mice, and confirmed their plasma expression in immunoassays. The plasma levels of anthrax toxin receptor 2 (ANTXR2), cadherin-13 (CDH-13), scavenger receptor cysteine-rich type 1 protein M130 (CD163), cartilage oligomeric matrix protein (COMP), Dickkopf-related protein 3 (DKK3), periostin, and secretogranin-1 were all confirmed to decrease with age. We then investigated whether any of the secreted proteins influenced bone metabolism and found that CDH-13 inhibited osteoclast differentiation. CDH 13 treatment suppressed the receptor activator of NF-kappa B ligand (RANKL) signaling pathway in bone marrow-derived macrophages, and intraperitoneal administration of CDH-13 delayed age-related bone loss in the femurs of aged mice. These findings suggest that low plasma CDH-13 expression in aged mice promotes aging-associated osteopenia by facilitating excessive osteoclast formation. Thus, CDH-13 could have therapeutic potential as a protein drug for the prevention of osteopenia.
Keywords: T-CADHERIN; COGNITIVE FUNCTION; ASSOCIATION; GROWTH; CDH13; DIFFERENTIATION; PROGRESSION; EXPRESSION; CLEAVAGE; CELLS